(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Dendroflora of the Tuzlovskie limany coast includes 86 species from 56 genera, 32 families, 22 orders, 3 classis and 2 divisions. There are 46 trees (53,5 %), 23 shrubs (26,7 %), 17 undershrubs (19,8 %) and one small shrub (Ephedra distachya). There are 10 dendrosozophytes (8 from IUCN Red List and 3 from Odessa Region Red List), among them 3 native species (Ephedra distachya, Periploca graeca, Tamarix ramosissima), two are Odessa region aboriginal flora components (Amygdalus nana та Quercus robur), one – other regions of Ukraine (Pinus pallasiana) and 4 – exotic species (Armeniaca vulgaris, Juglans regia, Platycladus orientalis, Robinia pseudoacacia). There are 5 highly invasive species in the park, among them 2 species-transformers (Amorpha fruticosa and Elaeagnus angustufolia). Dendrodiversity of the NNP “Tuzlovskie limany” formed by artificial forest areas Lebedevka, Yellow Jar and Tuzly mainly. There are 73,3 % all species. Plantations formed by 63 forest species, 32 of them are native (50,8 %) and 28 adventive (44,4 %) for Odessa region. Four forest species have gone beyong the forest areas and are the part of the steppe and psammophytic communities (Ailanthus altissima, Amorpha fruticosa, Elaeagnus angustifolia, Morus alba.). Native dendroflora includes 20 species (23,3 %), among them bushy tree, 2 shrubs, small shrub, 2 undershrubs and 14 small undershrubs.